Analysis Of Sapta Pesona Development Of Potential Tourist Attractions In Bongkasa Pertiwi Village, Abiansemal District, Badung Regency - Suarga, I Gusti Ngurah Made; Widnyani, Ida Ayu Putu Sri; Astawa, I Wayan (Jurnal Scientia, 2024)
This research aims to develop a strategy for implementing Sapta Pesona in an effort to increase tourism development at the tourist attraction in Bongkasa Pertiwi Village, Abiansemal District, Badung. The research method used is descriptive analysis by collecting data through observation, interviews and literature study. The results of the analysis identify tourism potential and the challenges faced by the destination. In facing potential, this research designs a strategy for implementing Sapta Pesona, namely natural beauty, cultural uniqueness, local wisdom, community friendliness, and security and order. Through this approach, it is hoped that destinations can attract the attention of tourists by utilizing local natural and cultural riches. The conclusion of this research is the importance of formulating a strategy based on the Sapta Pesona concept to increase the attractiveness and quality of tourism at the tourist attraction in Bongkasa Pertiwi Village.